Making R&D at MINT relevant to national development - Alang Md Rashid, Nahrul Khair (International Atomic Energy Agency (IAEA), 2001)
This paper attempts to identify issues facing nuclear research centres by tracing the development of the Malaysian Institute for Nuclear Technology Research (MINT). Approaches taken to arrive at the strategies in the areas of research and technology development, cooperation and technology transfer, and commercialization are highlighted. Interspersed in that review are some of the issues that are then collated in the Issues section.